Thyroid-neck phantom for use in nuclear medicine: patent review - Silva, Késsio Jhonys Pereira da (2022)
Anthropomorphic phantoms, commonly known as phantoms are devices that are widespread in several fields of knowledge, such as Nuclear Medicine, Physics, and Biomedical Engineering. These are used as a way to simulate organs of the human body to measure radioactive doses, to prevent humans from being subjected to too many doses of ionizing radiation. The present study aims to present a literature review on patents related to thyroid neck phantoms. From the results obtained in the literature, it was observed heterogeneity of patent deposits regarding the quantity in different countries and the recent activity of deposit of phantom objects in recent years, given that the study on their use and the registrations in responsible bodies were more frequent in the last ten years. In addition, it was found that there was a greater activity of patent deposits by public institutions of higher education when compared to the private sector.